An Effective Hybrid Firefly Algorithm with Harmony Search for Global Numerical Optimization. (20th November 2013) - Guo, Lihong; Wang, Gai-Ge; Wang, Heqi; Wang, Dinan
Abstract : A hybrid metaheuristic approach by hybridizing harmony search (HS) and firefly algorithm (FA), namely, HS/FA, is proposed to solve function optimization. In HS/FA, the exploration of HS and the exploitation of FA are fully exerted, so HS/FA has a faster convergence speed than HS and FA. Also, top fireflies scheme is introduced to reduce running time, and HS is utilized to mutate between fireflies when updating fireflies. The HS/FA method is verified by various benchmarks. From the experiments, the implementation of HS/FA is better than the standard FA and other eight optimization methods.